2013
DOI: 10.1080/03601234.2013.816603
|View full text |Cite
|
Sign up to set email alerts
|

Differences in response of two model estuarine crustaceans after lethal and sublethal exposures to chlorpyrifos

Abstract: This study assessed the in vitro and in vivo effects of an acetylcholinesterase enzyme inhibitor (chlorpyrifos) in two estuarine crustaceans: grass shrimp (Palaemonetes pugio) and mysid (Americamysis bahia). The differences in response were quantified after lethal and sublethal exposures to chlorpyrifos and in vitro assays with chlorpyrifos-oxon. Results from the in vitro experiments indicated that the target enzyme, acetylcholinesterase (AChE), in the two species was similar in sensitivity to chlorpyrifos inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Moreover, a role of neuronal control has been proved to regulate the periodic contractions of A. aurita body, in order to generate ring-vortices of the surrounding medium (Satterlie, 2002;Watanabe et al, 2009). In the aquatic environment, the CPF toxicity to marine organisms is well known, and the studies reported by some authors highlighted that the general pattern of the biological effects of this neurotoxic compound (OP) on the organism with a simple anatomical and physiological structure is different from that observed for other species belonging to higher level of biological organization (Key et al, 2013). For ephyrae of A. aurita exposed to CPF, the higher sensitivity for both end-points was particularly evident observing EC 50 values for % AFp and % I compared with LC 50 and EC 50 values of other model organism (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a role of neuronal control has been proved to regulate the periodic contractions of A. aurita body, in order to generate ring-vortices of the surrounding medium (Satterlie, 2002;Watanabe et al, 2009). In the aquatic environment, the CPF toxicity to marine organisms is well known, and the studies reported by some authors highlighted that the general pattern of the biological effects of this neurotoxic compound (OP) on the organism with a simple anatomical and physiological structure is different from that observed for other species belonging to higher level of biological organization (Key et al, 2013). For ephyrae of A. aurita exposed to CPF, the higher sensitivity for both end-points was particularly evident observing EC 50 values for % AFp and % I compared with LC 50 and EC 50 values of other model organism (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the inhibition of acetylcholinesterase (AchE) enzyme in the nervous system of vertebrate and invertebrate aquatic organisms has been established as a useful indicator of OP and CB pesticides exposure (Key et al, 2013). It has been shown that these neurotoxic compounds exert their effect at nervous system level, affecting the AchE, an enzyme that ensures the neurotransmission at synapses of neuromuscular and interneuronal junctions (Pope, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decapods of similar size to stage IV lobsters, chlorpyrifos LC50 ranges of 0.068 to 1.06 µg/L (24 h), 0.22 to 0.79 µg/L (48 h), and 0.029 to 0.69 µg/L (96 h) have been reported. These ranges are summarized from data established during studies of chlorpyrifos-exposed estuarine mysid (Americamysis bahia), daggerblade grass shrimp (Palaemonetes pugio), common prawn (Palaemon serratus), and European spider crab (Maja squinado), as well as freshwater Australian glass shrimp (Paratya australiensis; Bellas et al 2005;Key and Fulton 2006;Kumar et al 2010aKumar et al , 2010bKey et al 2013). Considering that the Health Canada LC50 range for aquatic invertebrates is 0.09 to 65 µg/L chlorpyrifos, a slight increase from these ranges is not an unexpected result (Pest Management Regulatory Agency 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of AChE after 96-h exposure to a 1.00-µg/L chlorpyrifos treatment has been correlated with abnormal chemotaxis and deterioration of feeding and locomotion in the amphipod crustacean G. fossarum (Xuereb et al 2009). Chlorpyrifos exposures of the freshwater amphipods Gammarus pulex and G. fossarum, adult and postlarval P. pugio, and adult A. bahia have provided AChE IC50 values of 0.027 to 1.23 µg/L (24 h) and 0.35 to 0.87 µg/L (96 h; Key and Fulton 2006;Xuereb et al 2007;Key et al 2013). The IC50s for cessation of normal movement calculated during the present study are comparable with these amphipod AChE IC50s, clarifying the link between AChE inhibition and survival-related movements further.…”
Section: Discussionmentioning
confidence: 99%